Hubungan Faktor Demografi dengan Literasi Kesehatan tentang Penyakit tidak Menular pada Lansia - Muhamad Anja Ahul Alaiha Kavit; Cahya Tri Purnami; Farid Agushybana; Dharminto Dharminto (Jurnal Manajemen Kesehatan Indonesia, 2022)
National development has an impact on Life Expectancy (UHH) to increase which causes the elderly group (elderly) to also increase, giving positive and negative effects. The negative effect of this increase is the increasing number of cases of PTM (Non-Communicable Diseases) in the community, especially in the elderly. The indirect cause of PTM in the elderly is due to the lack of ability to access, obtain, process, and digest information and know the most basic sources of health information or commonly referred to as health literacy. The factors related to the health literacy of elderly PTM include age, gender, education, occupation, income, access to health services. Lack of health literacy has an impact on decreasing the ability of individuals to access available health information, thus potentially causing errors in digesting information on health services that are being undertaken, thus causing an increase in the severity of the disease and even complications. This study aims to analyze factors related to health literacy of non-communicable diseases. The research method used was observational explanatory research using a sample of 90 people aged 60 years with PTM and had visited the Pegandan Health Center. The results of the study the majority of respondents were elderly (55.6%), female (73.3%), basic education (58.9%), not working (68.9%), low income (70%), accessing level 1 health facilities (92.2%), and using BPJS (56.7%). The conclusion of this research is that education variable (p-value=0.0001) and payment method (p-value=0.002) are related to health literacy about PTM.